PENGARUH PROFITABILITAS, SOLVABILITAS, LIKUIDITAS, DAN RASIO PASAR TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Yoga Adi Haryanto; Sudarno Sudarno (Diponegoro Journal of Accounting, 2019)
This research aims to examine the effect of Profitability, liquidity, solvency dan market ratio on going concern audit opinion on manufacturing companies that listed in Indonesian Stock Exchange (BEI) 2015 – 2017. The Dependent variable in this research is going concern audit opinion. The independet variables in this research are profitability, liquidity, solvency and market ratios.This research uses secondary data. The population of this research is manufacturing companies that listed in Indonesian Stock Exchange (BEI) 2015 – 2017. The research sample was selected using purposive sampling method and obtained 66 companies tha met the research citreria. Research test analysis using Logistic Regression Analysis.The result showed that profitability, solvency and market ratios had significantly influence the going concern audit opinion. While liquidity has no significantly effect on on going concern audit opinion.